2019
DOI: 10.1088/1757-899x/559/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Bagasse Sheets Reinforced with Nanofibrillated Celluloses

Abstract: The nanofibrillated celluloses (NFC) from different sources (i.e. bacterial cellulose (BC), pineapple leaf (PA) and banana pseudostem (BA)) were prepared using microfluidization. TEM and XRD results revealed diverse characteristics of the NFCs from different sources. Then, 0.1wt% of the prepared NFCs were integrated into the bagasse (BG) paper sheets. SEM images showed the densest surface of BG/NFC-BA sheet which also exhibited the highest sheet rigidity. Furthermore, the tensile tests indicated that the BG sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The reported density for each aerogel was calculated by estimating the corresponding contribution of cellulose and CNTs on each aerogel as Hernández‐Varela et al 17 reported before. Then, porosity (P, %) of each sample was calculated using this following equation : P%=1ρ*ρ×100 where (ρ*) is the experimental density, and (ρ) is the theoretical density of the aerogels calculated using the cellulose density (1.52 g/cm 3 ) and CNTs density (1.74 g/cm 3 ) reported elsewhere 34,35 and their respective mass fractions.…”
Section: Experimental Section/methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported density for each aerogel was calculated by estimating the corresponding contribution of cellulose and CNTs on each aerogel as Hernández‐Varela et al 17 reported before. Then, porosity (P, %) of each sample was calculated using this following equation : P%=1ρ*ρ×100 where (ρ*) is the experimental density, and (ρ) is the theoretical density of the aerogels calculated using the cellulose density (1.52 g/cm 3 ) and CNTs density (1.74 g/cm 3 ) reported elsewhere 34,35 and their respective mass fractions.…”
Section: Experimental Section/methodsmentioning
confidence: 99%
“…where (ρ*) is the experimental density, and (ρ) is the theoretical density of the aerogels calculated using the cellulose density (1.52 g/cm 3 ) and CNTs density (1.74 g/cm 3 ) reported elsewhere 34,35 and their respective mass fractions.…”
Section: Thermal Water Resistance and Mechanical Characterizationmentioning
confidence: 99%